THE IMPLEMENTATION OF PRONUNCIATION PRACTICE COURSE USING THE MINIMUM PAIR STRATEGY METHOD IN ENGLISH TEACHING - Hapsari Dwi Putri Ariyanti; Thohiriyah Thohiriyah (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2021)
The learning of English has its level of difficulty. One of its difficulties is pronunciation practice which is influenced by several factors. This study purposes to determine the factors that influence the difficulty in pronunciation practice. This study aims to implement a minimal pair strategy to facilitate learning pronunciation for students in one of the elementary schools in Temanggung as the object of this study. This study uses an experimental method by dividing a class of third-grade into two groups, namely the experimental group and the control group. By using this method, two different data will be generated to compare how effective the implementation of the minimum pair strategy is for elementary school students, especially for learning pronunciation.